2022
DOI: 10.3389/fevo.2022.856453
|View full text |Cite
|
Sign up to set email alerts
|

Traces of Genetic but Not Epigenetic Adaptation in the Invasive Goldenrod Solidago canadensis Despite the Absence of Population Structure

Abstract: Biological invasions may result from multiple introductions, which might compensate for reduced gene pools caused by bottleneck events, but could also dilute adaptive processes. A previous common-garden experiment showed heritable latitudinal clines in fitness-related traits in the invasive goldenrod Solidago canadensis in Central Europe. These latitudinal clines remained stable even in plants chemically treated with zebularine to reduce epigenetic variation. However, despite the heritability of traits investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 114 publications
(173 reference statements)
1
2
0
Order By: Relevance
“…Largely congruent with previous studies, we found no significant population structure of invasive S. canadensis (Figure 1 and Table S2) [41,42]. Meanwhile, we found that most sympatric (i.e., distributed at the same locality) individuals belonged to different genetic groups in China (Figure 1).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Largely congruent with previous studies, we found no significant population structure of invasive S. canadensis (Figure 1 and Table S2) [41,42]. Meanwhile, we found that most sympatric (i.e., distributed at the same locality) individuals belonged to different genetic groups in China (Figure 1).…”
Section: Discussionsupporting
confidence: 89%
“…Given that S. canadensis is highly self-incompatible, the absence of mixed genotypes highlights the important role of clonal reproduction in the survival and spread of S. canadensis, as observed in field experiments [27,28,43]. As for the relatively higher N e (which can be translated into relatively higher genetic diversity) observed in Group 1 when the founder effect began, one possible explanation could be the presence of genetic adaptation during its colonization in Europe, as reported recently by Eckert et al [42].…”
Section: Discussionmentioning
confidence: 54%
“…Czortek et al [40] also concluded that both local soil properties and functional diversity affect the performance of S. canadensis in its invasive range in central Europe. On the other hand, Eckert et al [41] pointed to some genetic, but not epigenetic adaptation processes of this species in its invasive range. Therefore, future studies on Solidago in central Europe should more strongly emphasize local and site-specific conditions and their impact on epigenetic variation.…”
Section: General Response Of S Gigantea Plants In Studied Locationsmentioning
confidence: 98%